EFEKTIVITAS MEDIA PEMBELAJARAN AUDIO VISUAL PADA HASIL BELAJAR SISWA KELAS V SDN 2 WALAHAR - Fuji Kirani; Mochamad Guntur (JKPD (Jurnal Kajian Pendidikan Dasar), 2023)
A low classification of fifth-grade students at SDN 2 Walahar’s outcomes and the limited utilization and application of diverse learning media in teaching and learning activities, particularly in scientific learning, served as the impetus for this study. This study aims to find the effectiveness of audio-visual-based media on student learning outcomes. With a one group pre-test and post-test design. 30 students in the fifth grade at SDN 2 Walahar made up the study's population. According to findings of the research, audio-visual learning materials are used by fifth graders at SDN 2 Walahar to improve their learning outcomes. This is demonstrated by the class V students at SDN 2 Walahar receiving an average score of 75.03 on the scientific portion of the pre test and an average score of 80.83 on the science portion of the post-test. The Paired Sample t-test showed a significant value of 0,000 in the research findings. The decision outcome of this study is that Ho is rejected while Ha is accepted because 0,000 is 0,005. The studying  findings support the idea that audio-visual learning materials can enhance fifth graders at SDN 2 Walahar's academic performance. This is demonstrated by the fact that, whereas grade V student learning outcomes tend to be acquired at a lower rate during the pre-test implementation phase than they do during the post-test phase, respectively.